Poisoned Streets: A Study on High-Purity Synthesis and Toxicological Profiling of Methamphetamine, MDMA, and Aminorex - Alizadeh Raef, Nima; Paknahad , Somayeh; Ghalari , Mohsen; Karimi Kashani , Mahdi; Hamedi, Fatemeh; Jafari , Mohanna; Gholipour , Maryam; Vishteh, Yasaman; Zargar, Fatemeh; Almasi , Bahareh; Asadi , Faeze; Khateri , Zahra; et al. (International Journal of Medical Toxicology and Forensic Medicine, 2025)
Background: This paper studies the toxicological assessment alongside high-purity synthesis of three psychoactive and degradative Methamphetamine, Aminorex, and MDMA. Methods: Each of these compounds was synthesized using novel methodologies, with an emphasis on purity, cartridge yield, and stereoisomeric resolution, where applicable. Analytical-grade products that could undergo toxicological profiling due to meeting rigorous retention criteria were guaranteed to undergo multistep purification and recrystallization. Results: The true pharmacological and toxicological, whether legal or illegal, is marked for each substance without the removal of contaminating impurities. Distinguished analytical capabilities, for instance, enabled the use of unparalleled analytical methods to correlate some articulated nuclei with their respective neurophysiological, as well as systemic, reactionary constructs. A toxicological and purification prerequisite comparison of the compounds revealed an inequality. Methamphetamine, Aminorex, and ecstasy posed the most neurotoxic potential, while Aminorex and ecstasy posed distinct risks of decomposition. Conclusion: This sets the framework for synthesis evaluation in toxicological research and forensic analysis.